Implementasi Algoritma Weighted Product Untuk Penilaian Quis Pada Aplikasi Belajar Online Siswa Sekolah Menengah Kejuruan - Yuza Reswan; Pahrizal Pahrizal; Erwin Dwika Putra; Sahrudin Sahrudin (UNIVED Press, 2024)
Online learning media (Online learning) uses a technological approach that is more suited to today's student learning systems compared to conservative methods of learning in the classroom. By looking at the varying number of questions, the weighting of the exercises varies with the number of questions contained in the exercises. As for the examples of questions that consist of 20 questions, each question is worth 5, so if the student answers 20 questions correctly then the student gets a score of 100. The problems encountered in research on citizenship education learning are still manual so that students' understanding of the concepts and rules of citizenship education is still limited. less because it is rote. The problem formulation based on the background above is that the weighting of the questions and answers is not yet known. The benefit of this research is as an information medium to introduce quiz exercises in applications with citizenship education subject matter for students at Vocational High School 08, North Bengkulu Regency with the concept of learning while playing.